Enhanced Protein Damage Clearance Induces Broad Drug Resistance in Multitype of Cancers Revealed by an Evolution Drug‐Resistant Model and Genome‐Wide siRNA Screening. Issue 23 (11th October 2020) - Shao, Fangyuan; Lyu, Xueying; Miao, Kai; Xie, Lisi; Wang, Haitao; Xiao, Hao; Li, Jie; Chen, Qiang; Ding, Renbo; Chen, Ping; Xing, Fuqiang; Zhang, Xu; et al.
Abstract: Resistance to therapeutic drugs occurs in virtually all types of cancers, and the tolerance to one drug frequently becomes broad therapy resistance; however, the underlying mechanism remains elusive. Combining a whole whole‐genome‐wide RNA interference screening and an evolutionary drug pressure model with MDA‐MB‐231 cells, it is found that enhanced protein damage clearance and reduced mitochondrial respiratory activity are responsible for cisplatin resistance. Screening drug‐resistant cancer cells and human patient‐derived organoids for breast and colon cancers with many anticancer drugs indicates that activation of mitochondrion protein import surveillance system enhances proteasome activity and minimizes caspase activation, leading to broad drug resistance that can be overcome by co‐treatment with a proteasome inhibitor, bortezomib. It is further demonstrated that cisplatin and bortezomib encapsulated into nanoparticle further enhance their therapeutic efficacy and alleviate side effects induced by drug combination treatment. These data demonstrate a feasibility for eliminating broad drug resistance by targeting its common mechanism to achieve effective therapy for multiple cancers. Abstract : Many anticancer drugs can induce protein damage, which is a common way to kill cancer cells. Meanwhile, the damaged proteins trigger mitochondrial protein import surveillance checkpoint which impairs mitochondrial respiration activity, leading to the activation of proteasome and clearance of damaged proteins. This feedback loop triggers broad drug resistance, which is overcome by proteasome inhibitors.